Penggunaan Art Teraphy Dalam Mengatasi Depresi Siswa Pasca Lanjut Perguruan Tinggi - Hake Ramalia Sentika; Yeni Karneli (KONSELING: Jurnal Ilmiah Penelitian dan Penerapannya, 2021)
Art Therapy is a combination of two scientific disciplines, namely art and psychology, which produces an interesting technique. The resulting integration of these two theories focuses more on how and why art therapy is useful as a primary intervention and as a modality. Guidance and counseling services in schools can be provided through direct services or through the media. This service uses a variety of methods. One interesting method that can be used in helping students / counselees is to use art therapy. Mood disorders which are characterized by gloom and deep and continuous sadness resulting in loss of excitement in life, not experiencing disturbances in assessing reality (reality testing ability / RTA, still good), personality remains intact (not experiencing splitting of personality ) behavior can be disturbed but within normal limits is said to be depressed.